(untitled) (Czech Journal of International Relations, 1997)
We have before us the second edition of Weber’s publication Kleine Geschichte der DDR, which deals with the still intensively researched topic - the "image of history" of the German Democratic Republic (GDR). At the time of the first publication of this book (i.e. in 1980), the GDR had not yet appeared as a stable state. Considering the events that took place during the following ten years, it is certainly important and interesting to deal with the internal political development of the GDR, even in a broader context. In the former GDR, the "image of history" occupied a central place in ideology. Historical events were distorted under ideological influence, historiography was supposed to support politics. Therefore, in his book, Hermann Weber tried to clearly and truthfully organize the historical facts of the development of the GDR. It is a chronological overview of the history of the GDR since 1945. Attention it is focused primarily on the political system, on socio-economic development and on the involvement of the GDR in the Soviet bloc. Numerous documentary testimonies and quotes help to flesh out the authentic testimony.